Learn to code with Ruby - Paskhaver, Boris (Packt Publishing, 2017)
"The most comprehensive Ruby course available. An in-depth overview of coding with Ruby, a popular programming language renowned for its simplicity and elegance. Whether you've never written a line of code before or are looking to learn a brand new language, this course covers all bases! Ruby is a language released by Yukihiro Matsumoto in 1995 that bills itself as 'a programmer's best friend'. Every aspect of Ruby is designed to make programming easier for the developer. There is no better first language if you're interested in learning how to program. Ruby also serves as the foundation for Ruby on Rails, a popular web framework that powers over 1.2 million websites worldwide. The course offers an extensive introduction to the base language you'll need to know if you intend to tackle web development in the future. Check out the sample videos below to get a taste of what the course has to offer! So if you're ready to commit yourself, if you're eager to expand your knowledge of programming, if you're ready to discover what makes this elegant language so loved by developers, you are ready to Learn to Code with Ruby! Thanks for checking out the course!"--Resource description page